Anti-snoring device controlled by Arduino Uno - Phua, Brandon Jun Ming. (Universiti Malaysia Sarawak (UNIMAS), 2017)
This project present the solution for sleeping disorder by using an Anti Snoring Device Controlled by Arduino Uno. The purpose of this project is to create a device that eliminate or reduce snoring through electronic concept; detection of snoring and feedback of the system. Detection of snoring operated through analyzing snoring noise and vibration produced by the user. The feedback of the system is use to awake the person which indicate that they need to change their sleeping position. This project focusing on the changes in sleeping position in order for the user to adjust the airway path and prevent from sleeping on their back. In fact, the tendency of snoring is higher if the user sleep in supine position (on back) compared to lateral position (on side). In addition, this project provide the solution of snoring without contribute any side effects to the user. This device operated inside the designated pillow, which is the final product of this project.